Developing a Professional Standard of Care for Academic Advisors of Student Athletes: Use of Information Based Formative Evaluation in Academic Support - Bruno, James E. (My University, 1989)
Assisting ill prepared student athletes, many of whom are recruited from our nation's inner city schools, in their adjustment to a rigorous college level academic program is a formidable challenge for an academic support program. Building off of Bruno et al. (1987) ,this study attempted to underscore the need for establishing, what might be termed, a ''standard of professional care'' for academic support personnel that is based on the formative evaluation of the student athlete's instructional needs. In this study the use of the information referenced testing (IRT) concept for addressing student athlete information needs was explored and the results of an experiment involving eight N4A institutions were reported. IRT was seen as a cost-effective testing method and its output was an IEP. The test could provide a true picture for what support services students need over the results of a standardized test such as the SAT.
Keywords: academic predictors; at-risk